2020
DOI: 10.1016/j.robot.2019.103330
|View full text |Cite
|
Sign up to set email alerts
|

Enabling garment-agnostic laundry tasks for a Robot Household Companion

Abstract: To those who sacrificed their precious time doing laundry. [6] Raul Fernandez-Fernandez, David Estevez, Juan G Victores, and Carlos Balaguer. "Reducing the number of evaluations required for CGDA execution through Particle Swarm Optimization methods." In: IEEE International Conference on Autonomous Robot Systems and Competitions (ICARSC). IEEE. 2017, pp. 284-289.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…In contrast to this vision of home robotic companions, research has also shown that not all people accept this role for robots (Deutsch et al, 2019) and that preferred roles may be those of a butler or an assistant rather than that of a friend (Dautenhahn et al, 2005). An additional major application area of robots in the home is domestic chores (Cakmak & Takayama, 2013), such as floor cleaning Prassler et al, 2000), organizing (Pantofaru et al, 2012), laundry (Estevez et al, 2020), and kitchen assistance (Pham et al, 2017).…”
Section: Robots In the Homementioning
confidence: 99%
“…In contrast to this vision of home robotic companions, research has also shown that not all people accept this role for robots (Deutsch et al, 2019) and that preferred roles may be those of a butler or an assistant rather than that of a friend (Dautenhahn et al, 2005). An additional major application area of robots in the home is domestic chores (Cakmak & Takayama, 2013), such as floor cleaning Prassler et al, 2000), organizing (Pantofaru et al, 2012), laundry (Estevez et al, 2020), and kitchen assistance (Pham et al, 2017).…”
Section: Robots In the Homementioning
confidence: 99%
“…Mobile manipulators for indoor human environments have the potential to serve as versatile devices that perform a variety of useful tasks. Examples from the literature include assisting people with disabilities [1]- [5], delivering medicine [5]- [7], cleaning [8]- [10], organizing [11]- [13], folding laundry [14]- [16], and entertaining [17], [18]. To date, mobile manipulators have primarily been used in robotics research labs.…”
Section: Introductionmentioning
confidence: 99%